TINJAUAN SEJARAH TERHADAP NASKAH DAN TEKS KITAB PENGETAHUAN BAHASA, KAMUS LOGAT MELAYU JOHOR PAHANG RIAU LINGGA KARYA RAJA ALI HAJI - Ellya Roza (Sosial Budaya, 2012)
Kingdom of Riau in the 19th century recognized by many historians as the center of culture and intellectual development. While at the same time, the kingdom of Riau no longer holds hegemony and succeeding in politics, economy and trade, but they have a tradition of excellence in the form of writing that many writers with works of quality that is not only in the field of literature and language alone but also in the fields of religion, history, socio-political, legal, and cultural. Although the tools for writing like paper and ink difficulty encountered in those days, and must be imported from European countries, but the author and the author's Riau while still concentrating on the activities making up the reef. For instance, Raja Ali Haji (1808-1873) is the third descendant of Raja Haji Fi Sabilillah most productive in writing activities. One of his works, entitled The Book of Knowledge of Language, Slang Dictionary Pahang Malay Johor Riau linga which was completed in 1858 is a Malay Dictionary Malay First Nature books can even be regarded as Malay Einsiklopedi containing approximately 2000 sentences basic and advanced script written as Bustanul Katibin which intends to foster Malay language became the language of the standard on its own. The manuscript of the book, now the mistress Foundation Indrasakti in Penyengat. In connection with that paper will review the history of the manuscript and are contained in the text.